Formulation for flutter and vibration analysis of a hingeless helicopter blade in hover: Part I - Ozdemir Ozgumus, Ozge; Kaya, Metin O. (Emerald, 2007)
PurposeThis study aims to derive the kinetic and the potential energy expressions of a rotating uniform hingeless rotor blade and the aerodynamic loads that act on the blade element in hovering flight conditions.Design/methodology/approachThe blade is modeled as an Euler‐Bernoulli beam. The governing partial differential equations of motion and the associated boundary conditions are derived using the Hamilton's principle.FindingsThe derivations of the energy expressions and the aerodynamic loads are made in a detailed way by including several explanatory tables. The resultant equations of motion are in good agreement with the literature. Additionally, in this work the hub radius effect is included in the equations of motion.Originality/valueArguably this study achieves a breakthrough in deriving the kinetic and the potential energy expressions of a rotating uniform hingeless rotor blade and the aerodynamic loads that act on the blade element in hovering flight conditions.